LXIX Open Seminar on Acoustics Karpacz, Poland, September 25 – 29, 2023 - on Acoustics, LXIX Open Seminar (Archives of Acoustics, 2023)
On September 25–29, 2023, the LXIX Open Seminar on Acoustics OSA2023 was held in Karpacz. The conference was organized by the Wroclaw Branch of the Polish Acoustical Society (PTA). Simultaneously with the OSA2023 conference two accompanying events were held: Signal Processing Symposium SPSympo23 and 5th Polish-German Structured Conference on Acoustics PGSCA2023. 240 specialists from Poland and abroad took part in the OSA2023, SPSympo23, and PGSCA23 conferences delivering 96 papers and 6 plenary presentations.